Green synthesis and characterization of silver nanoparticles using Pteris vittata extract and their therapeutic activities. (2nd September 2021) - Jha, Anal Kant; Zamani, Sabiha; Kumar, Antresh
Abstract: The bacterial infections have been substantially increasing with higher mortality and new regimens required for their management. The present work deals with the green synthesis of silver nanoparticles (AgNPs) using leaf extract of Pteris vittata at pH 9.0. The AgNPs showed a single absorption peak at 407 nm. The morphology of AgNPs was found to be spherical in shape analyzed by scanning electron micrographs. The X‐ray diffraction studies revealed the face‐centered cubic structure of AgNPs with a 17‐nm average crystallite size. They showed the antimicrobial activity against Pseudomonas aeruginosa, and the cell growth was completely ceased at the minimum inhibitory concentration (MIC); 100 μg/mL, with rapidly decreased cell viability. This bactericidal effect was due to the enhancement of cell permeability caused by cell disruption. The AgNPs lead to show a promising antiquorum‐sensing activity by inhibition of toxin protease and pyocyanin in P. aeruginosa by 88% and, 94% respectively, at the sub‐MIC concentration (0.25× MIC). These results conclude that the green synthesis of AgNPs shows a promising antimicrobial and antivirulence activity against P. aeruginosa . Abstract : Antimicrobial effect of?green nanoparticles of Pteris vittata